Assessing the accuracy of measurements obtained by dual-energy X-ray absorptiometry on pig carcasses and primal cuts. (February 2019) - Kipper, M.; Marcoux, M.; Andretta, I.; Pomar, C.
Abstract: Accuracy, trueness, and precision of dual-energy X-ray absorptiometry (DXA) assessment of pig carcasses and primal cuts dissected tissues were evaluated using available region of interests (ROI) and Total Body and Small Animal software modes. Fat mass, lean mass, and bone mineral content (BMC) DXA values were compared to dissected tissue weights (fat, muscle, and bones). Used ROI influenced ( P < 0.05) DXA measurements of BMC, fat mass, and lean mass. Configuration modes influenced (P < 0.05) DXA fat mass in shoulders and bellies, whereas BMC estimates differed (P < 0.05) among configuration modes. Equations predicting dissected composition on the basis of DXA measurements showed high coefficients of determination, particularly for fat and lean masses. DXA is able to accurately evaluate the composition of pig carcasses and primal cuts. From a methodological viewpoint, and considering the variations observed in this study, the method for image acquisition and analysis should be chosen on the basis of the item to be evaluated.